Plasma Brain‐Derived Neurotrophic Factor (BDNF) and serum cortisol levels in a sample of workers exposed to occupational stress and suffering from Adjustment Disorders. Issue 7 (14th June 2019) - Buselli, Rodolfo; Veltri, Antonello; Baldanzi, Sigrid; Marino, Riccardo; Bonotti, Alessandra; Chiumiento, Martina; Girardi, Michelle; Pellegrini, Luca; Guglielmi, Giovanni; Dell'Osso, Liliana; Cristaudo, Alfonso
Abstract: Introduction: Decreased plasma BDNF (pBDNF) levels have been proposed as a biomarker in illness phases of mood disorders. Serum cortisol (seC) levels are an index of energy mobilization and stress. The aim of this cross‐sectional study was to evaluate pBDNF and seC levels in workers exposed to occupational stress and suffering from Adjustment Disorders (AD) compared to healthy workers. Methods: Plasma BDNF and seC levels were measured by means of specific immunoassays in 64 AD patients and 38 healthy controls. Perceived and occupational stress was evaluated in patients and controls using the Psychological Stress Measure (PSM) and the Job Content Questionnaire (JCQ). Psychopatological symptoms in patients were assessed using specific rating scales. Results: Plasma BDNF levels resulted significantly higher in patients than in controls, whereas no significant differences were found for seC levels. In patients but not in controls pBDNF levels showed a significant positive correlation with seC levels. Perceived stress levels were positively correlated with all psychopatological rating scales scores. Conclusions: BDNF could play a key role in the pathophysiology of stress‐related disorders and its peripheral levels elevation could contribute to protect neurons under stress. Further research is needed focusing on biomarkers for stress‐related disorders as a potential tool for the diagnosis and prevention of occupational diseases. Abstract : In this study a group of workers exposed to occupational stress and suffering from Adjustment Disorders (AD) exhibited plasma BDNF levels significantly higher than those of healthy controls. In patients but not in controls plasma BDNF levels showed a significant positive correlation with serum cortisol levels. BDNF could play a key role in the pathophysiology of stress‐related disorders and its peripheral levels elevation could contribute to protect neurons under stress. Further research is needed focusing on biomarkers for stress‐related disorders as a potential tool for the diagnosis and prevention of occupational diseases.